Internalisasi Nilai Musāwah (Kesetaraan) dalam Pembelajaran Pendidikan Agama Islam (PAI) Kelas VII di SMP Giki 1 Surabaya - Khoirun Nisa; Ali Ahmad Yenuri (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to comprehensively examine the internalization of the value of Musāwah (equality) in Islamic Religious Education (PAI) for seventh graders at SMP Giki 1 Surabaya, emphasizing the process of internalization of the value of musāwah. A descriptive qualitative approach was used to collect data through in-depth interviews with the principal, vice principal for curriculum, PAI teachers, and Muslim and non-Muslim students, supplemented by direct observation of the dynamics of the school environment. The results show that the internalization of the value of musāwah occurs through three main stages: value transformation through material delivery, value transactions through dialogue and group discussions, and transinternalization through teacher role models and habituation in inclusive school policies. The school consistently applies the principle of non-discrimination, provides equal participation space, and assesses not only academic achievement but also students' social attitudes. These findings indicate that the value of equality does not stop at the conceptual level, but grows into a dynamic school culture, reflected in mutual respect, interfaith cooperation, and minimal conflict based on differences. Thus, the internalization of the value of Musawah in Islamic Religious Education (PAI) learning has proven effective in shaping students' character to be tolerant, inclusive, and able to live harmoniously in diversity.